2019
DOI: 10.5430/cns.v7n3p58
|View full text |Cite
|
Sign up to set email alerts
|

Comparing warm compresses application vs. chilled cabbage leaves for relieving breast engorgement among post-natal mothers

Abstract: Background: Breast engorgement is a common problem among postnatal women worldwide, some of whom use warm compresses to promote vasodilatation, improve circulation, and promote the amount of milk produced by the breasts. Conversely, the application of chilled cabbage leaves can reduce pain, the firmness of the engorged breasts, and prolong breastfeeding duration.Purpose: To examine the effect of warm compresses application as compared to chilled cabbage leaves for relieving breast engorgement and pain.Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
0
0
2
Order By: Relevance
“…According to Eittah and Ashour’s [ 17 ] results, which concurred with those of the current study, the mean pain scores for both groups improved after the use of hot compresses and cold cabbage leaves; the improvement was highly statistically significant. Consistent improvement was seen between the second and sixth applications.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…According to Eittah and Ashour’s [ 17 ] results, which concurred with those of the current study, the mean pain scores for both groups improved after the use of hot compresses and cold cabbage leaves; the improvement was highly statistically significant. Consistent improvement was seen between the second and sixth applications.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, in line with the findings of the current study, Eittah and Ashour’s [ 17 ] findings demonstrated that there were no statistically significant differences in terms of age and education level between the study participants (p ≥ .05). Napisah et al [ 16 ] also revealed that the majority of respondents were in good health and of reproductive age, had high school education, were multiparous, and delivered their babies via cesarean section surgery.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Meme dolgunluğu doğum sonu dönemde sık karşılaşılan bir durum olmasına rağmen ülkemizde meme dolgunluğunu değerlendirmek için kullanılan geçerli ve güvenilir bir ölçüm aracı bulunmamaktadır. Pamela Dee Hill ve Sharron Smith Humenick (1994) tarafından geliştirilen Meme Dolgunluğu Değerlendirme Skalasının uluslararası çalışmalarda yaygın olarak kullanıldığı belirlenmiştir (7,(9)(10)(11)(12)(13). Ülkemizde laktasyon dönemindeki kadınlarda meme dolgunluğu belirlemek üzere bir ölçüm aracı bulunmaması nedeniyle, bu çalışmada Meme Dolgunluğu Değerlendirme Skalasının Türkçe literatüre kazandırılması için psikometrik özelliklerinin incelenmesi amaçlanmıştır.…”
Section: Introductionunclassified
“…Daun kubis mengandung sinigrin (allylisothiocyanate) rapine, mustardoil, magnesium, oxylate, dan sulfur dan memiliki sifat antibiotik, anti-iritasi, dan anti inflamasi. Kandungan daun kubis membantu dalam meningkatkan perfusi darah ke daerah pembengkakan, melebarkan kapiler dan bertindak sebagai penghalau counter sehingga mengurangi pembengkakan dan peradangan payudara sehingga susu mengalir(Eittah and Ashour, 2019).Hasil penelitian ini diperkuatMasoud et al (2018) yang menyatakan bahwa daun kubis efektif untuk mengurangi pembengkakan payudara. Menurut penelitian tersebut, daun kubis lebih efektif dan memberikan efek pemulihan yang cepat pada pembengkakan payudara serta murah dan mudah diperoleh.…”
unclassified